SOSIALISASI NILAI-NILAI ISLAM DALAM MENCEGAH POLITIK IDENTITAS DAN POLARISASI SOSIAL DI DESA CIPANCUH, GANTAR, INDRAMAYU - Rahim, Abdur; Munawar, Kholil Al; Riyadi, Sugeng; Hamdan, Hamdan; Shofi, Ahmad; Sohardono, Herry; Salam, Shoffan Abdus; Carkid, Carkid; Lestari, Fitha Dieni Puja; Dewanti, Tri Mustika; Rijal, Ahlan Khoir Syah; Fathoni, Ali (Jurnal Abdimas Bina Bangsa, 2025)
Identity politics and social polarization are growing challenges in Indonesian society, including at the village level. These phenomena can lead to social fragmentation and hinder community development. This Community Service Program (PkM) aims to socialize Islamic values as a solution to prevent identity politics and social polarization in Cipancuh Village, Gantar District, Indramayu. The method used in this activity is a participatory approach with a community-based counseling model through lectures, group discussions, and educational media. The results indicate an increased understanding among community members regarding the dangers of identity politics and the importance of unity in Islam. Participants have also begun adopting the values of brotherhood (ukhuwah), justice, and tolerance in their social lives. This activity recommends follow-up programs involving village governments, educational institutions, and religious leaders to strengthen religious moderation and build a harmonious and inclusive society.